2002
DOI: 10.1007/s11661-002-0144-z
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of point defect diffusion in alpha-zirconium

Abstract: Two types of intrinsic defect, i.e., vacancy and self-interstitial atom (SIA), are formed in metals during irradiation with energetic particles. The evolution of defect population leads to significant changes in microstructure and causes a number of radiation-induced property changes. Some phenomena, such as radiation growth of anisotropic materials, are due to anisotropy in the atomic mass transport by point defects. Detailed information on atomic-scale mechanisms is, therefore, necessary to understand such p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 21 publications
3
32
0
Order By: Relevance
“…On the other hand, MD simulations have also been used to study the mobility of defects in a-Zr [3]. These simulations show that single interstitials move in one dimension in the basal plane.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, MD simulations have also been used to study the mobility of defects in a-Zr [3]. These simulations show that single interstitials move in one dimension in the basal plane.…”
Section: Introductionmentioning
confidence: 99%
“…Holt and Gilbert (1986) examined the hci type dislocation loop of annealed zircaloys under a high fluence with 8.6 Â 10 25 n/m 2 between 553 and 584 K. In these results, hci-loops were observed for annealed zircaloy-2 and zircaloy-4 at greater than 3.0 Â 10 25 n/m 2 , while hai-loops were only shown for specimens irradiated with fluence below 3.0 Â 10 25 n/m 2 . Further work by many authors confirmed that hai-loops nucleate from the beginning of the irradiation, while hci-loops form above a threshold dose only, indicating that the kinetics of the formation of hai and hci-type loops differ (Bacon, 1993;Carpenter et al, 1981Carpenter et al, , 1988Frank, 1988;Holt and Gilbert, 1986;Hood, 1988;Jostsons et al, 1977aJostsons et al, , 1977bNorthwood et al, 1979;Osetsky et al, 2002;Pasianot and Monti, 1999;Was, 2007;Woo, 1979;Woo, 1988Woo, , 2000Woo and Liu, 2009). …”
Section: Dislocation Loopsmentioning
confidence: 97%
“…Molecular dynamics simulations of formation energies of interstitial clusters show high stability of these clusters, with binding energies on the order of 2 eV. Jump frequencies for self-interstitials were taken from the function [5,6] …”
Section: Temperature Dependence Of Damage Accumulation In Hcp Metalsmentioning
confidence: 99%
“…The migration energy for single vacancies is 0.93 eV [5] with an attempt frequency of 1.22 · 10 14 s À1 . Further details of the parameters used are given in Refs.…”
Section: Temperature Dependence Of Damage Accumulation In Hcp Metalsmentioning
confidence: 99%
See 1 more Smart Citation